Design Optimization of Linseed Thresher for Higher Efficiency - Geeta Patel; Sourabh Kumar Dewangan1; R.K. Naik (International Journal of Manufacturing and Production Engineering, 2024)
Linseed, a valuable Rabi crop grown for both grain and fiber, has seen rising demand across industries, boosting interest in optimizing its production processes. Recognizing this, SVCAET and RS at IGKV Raipur conducted a study focused on improving the design and efficiency of linseed threshing technology. The research aimed to develop an optimized head cut type linseed thresher, addressing both design and performance factors. Three distinct prototypes were designed, varying in concave and threshing drum specifications. Design optimization was conducted across various parameters to enhance the performance of each unit. Specifically, the study examined three peripheral speeds (10.5, 12.5, and 14.5 m/s), three types of threshing cylinders (peg, canvas, and a hybrid of peg and canvas), and three concave opening sizes (3, 4, and 5 mm) to determine the ideal configuration. This approach sought to maximize threshing effectiveness while maintaining grain quality and minimizing fiber damage. The findings of this research provide crucial insights for increasing the efficiency and durability of linseed threshers, making them more viable for widespread agricultural use.
Keywords: Linseed thresher; Optimization; design parameters and peripheral speed; threshing efficiency